Uterine tube adenoma in a bitch - Pierezan, Felipe; Trost, Maria E.; Barros, Claudio S. L. (Brazilian Journal of Veterinary Pathology, 2016)
An adenoma of the uterine tube in a 14-year-old, mixed breed, female dog with history of abdominal distention is described. Ultrasonographic examination revealed a 15 x 20 cm anechoic mass in the left caudal region of the abdominal cavity. Laparotomy was performed and the mass, within the left ovarian bursa, was surgically excised by ovariohysterectomy. Grossly, the left ovarian bursa was markedly increased in size (7 x 15 x 20 cm) and contained approximately 300ml of serosanguineous fluid that surrounded a 5 x 13 x 17 cm in diameter, red, papilliform, and soft mass. Histologically, the mass was characterized as an epithelial neoplastic proliferation arranged in a papilliform pattern. The numerous papillae were lined by a single layer of well-differentiated columnar ciliated cells, with occasional cuboidal cells, and supported by a dense fibrovascular stroma. Columnar cells contained abundant, slightly vacuolated and granular cytoplasm. The granules were located predominantly in the apical surface and were Alcian blue and periodic acid-Schiff positive. Nuclei were round and polarized in the apical surface of the cell. Neoplastic cells were positive for pan-cytokeratin and vimentin. The diagnosis of adenoma of uterine tube was based on the anatomic location, and histological, immunohistochemical and ultrastructural findings.